Learning differentiated curriculum design in higher education - Moye, John N. (Bingley, U.K. : Emerald Publishing Limited, 2019)
As the complexity of 21st century disciplines has increased it has become necessary to rethink the design and delivery of learning to more effectively serve the diverse needs and learning styles of students in higher education. While instructional design and instructional technologies have advanced quickly, the processes of curriculum design have fallen behind.This book presents a comprehensive, systematic approach to the development of curricula in higher education in which each component is configured to optimize learning. The approach is based in an analysis of the psychophysics of the learner and employs theories of learning, instruction, and environment to design each component. The result of this process is the development of curricula that demonstrate optimal design attributes, remove barriers to learning, and expedite the learning. By presenting methods that provide practical, effective and efficient strategies to ensure an inclusive curriculum for all learners, this book will prove invaluable for higher education leaders, practitioners, and curriculum designers.
Prelims -- A shared definition of curriculum design -- A design approach to curricula -- Differentiating the dimensions of curriculum -- Differentiated curriculum -- Evaluating curricula -- Summary and conclusions -- Afterword -- References -- Index.
Includes bibliographical references and index.
Keywords: Curriculum planning; Individualized instruction; Individualized education programs; Education -- Higher; Education